2016
DOI: 10.1039/c6fd00025h
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and orientation of catalytic Janus colloids at the surface of water

Abstract: Janus colloidal particles show remarkable properties in terms of surface activity, self-assembly and wetting. Moreover they can perform autonomous motion if they can chemically react with the liquid in which they are immersed. In order to understand the self-propelled motion of catalytic Janus colloids at the air-water interface, wetting and the orientation of the catalytic surface are important properties to be investigated. Wetting plays a central role in active motion since it determines the contact between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 55 publications
3
54
0
Order By: Relevance
“…The behavior of self-propelling silica/Pt particles at air-water interfaces has been recently investigated by Wang et al [28,29], showing both analogies and striking differences when compared with our observations. These authors similarly reported larger values of some rotational diffusion times and a consequent enhancement of the persistence length of the corresponding active trajectories.…”
Section: Discussionsupporting
confidence: 62%
“…The behavior of self-propelling silica/Pt particles at air-water interfaces has been recently investigated by Wang et al [28,29], showing both analogies and striking differences when compared with our observations. These authors similarly reported larger values of some rotational diffusion times and a consequent enhancement of the persistence length of the corresponding active trajectories.…”
Section: Discussionsupporting
confidence: 62%
“…We have revealed an enhancement of their two dimensional active motions compared to the bulk [28] [29]. In this paper, we report new experimental results on their rotational Brownian motion extending our first observations on the slowing down of the perpendicular and parallel rotational diffusion coefficients, Dr, and Dr,|| [27,29]. A model for the rotational friction is also developed in order to describe our experimental findings.…”
Section: Introductionsupporting
confidence: 57%
“…Rotational Brownian diffusion is also a key parameter that sets the persistence of active motion of self-propelled colloids [26]. Janus spherical silica particles half coated with a thin platinum layer are such particles, self-propelling in presence of hydrogen peroxide [27]. Recently, we have studied their behaviour at the air/water interface.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, when the microswimmer approaches a passive particle ( Fig. 2(g) and Video S7 [22]), its direction of motion (blue arrow) changes from the one observed before the collision and no longer corresponds to the 2D projection of the particle asymmetry (green arrow, note that in 2(g) a 20 nm Pt-layer is used to visualize the cap and this choice leads to a metastable tilted orientation [27]). Eventually, the microswimmer escapes the passive obstacle in a random direction (inset to the bottom-right panel in Fig.…”
mentioning
confidence: 99%